Views on aging and emotional benefits of physical activity: effects of an exercise intervention in older women - Klusmann, Verena; Evers, Andrea (Psychology of sport and exercise, 2012)
Objectives This intervention study evaluated the effects of exercise in old age on views on one’s own aging and on direct approach motivation for physical activity. It further examined the mechanism between these variables.Design Two hundred forty-seven healthy women aged 70−93 years were randomized to an exercise course (n = 86), an active (n = 85), or a passive control group (n = 76) for a 6-month participation in Berlin, Germany. Activity interventions (3 × 1.5 h/wk) were conducted using standardized manuals.Method Group differences in changes of views on aging and direct approach were evaluated by analyses of covariance adjusted for baseline. A mediating effect of direct approach between exercise participation and views on aging was tested with percentile-based bootstrapping.Results In contrast to both the active and the passive control groups, higher direct approach, F(2, 226) = 6.97, p = .001, and less aging dissatisfaction, F(2, 225) = 5.39, p = .005, were observed in the exercise group after 6 months. Exercise had an indirect beneficial effect on aging dissatisfaction through direct approach, B = −0.31, 95% CI = −0.68 to −0.05.Conclusion In women above 70 years, exercise participation increases direct approach motivation which in turn leads to lower aging dissatisfaction. This shows that exercise holds the potential to overcome subjective ageist bias.